Durability of Wearable Antennas Based on Nonwoven Conductive Fabrics: Experimental Study on Resistance to Washing and Ironing - Laura Corchia; Giuseppina Monti; Luciano Tarricone (International Journal of Antennas and Propagation)
Adhesive nonwoven conductive fabrics are appealing materials for fabricating fully textile antennas for wearable wireless systems. Wearable antennas should be flexible, lightweight, and mechanically resistant. Additionally, the antenna performance should be robust to activities related to daily use of garments, such as washing and ironing. Accordingly, in this work, the results of several washing tests performed on fully textile antennas fabricated by exploiting three different adhesive nonwoven conductive fabrics are reported.